Estimation of nutrient excretion factors of broiler and layer chickens in Japan. (2nd August 2016) - Ogino, Akifumi; Murakami, Hitoshi; Yamashita, Takahiro; Furuya, Motohiro; Kawahara, Hirofumi; Ohkubo, Takako; Osada, Takashi
Abstract: We estimated the nitrogen (N), phosphorus (P), potassium (K) and magnesium (Mg) excretion factors of broiler and layer chickens in Japan, using two approaches and the latest data available. In the top‐down approach, we determined the nutrient amounts in the feeds and those in the products (i.e. the liveweight gain, eggs), and the national nutrient excretions were determined as the difference between these amounts. We then calculated the nutrient excretion factors by dividing the national excretions by the number of animals. In the bottom‐up approach, we calculated the amounts of nutrients in the feed and product per head using productivity parameters (feed conversion ratio, etc.). The differences between these amounts were considered the nutrient excretion factors. The average nutrient excretion factors of broilers (g/day/head) estimated using the top‐down and bottom‐up approaches were: N, 1.40 and 1.87; P, 0.36, 0.50; K, 0.54, 0.77; Mg, 0.13, 0.18, respectively. The excretion factors obtained by the top‐down approach can be used to calculate the national/regional excretions. The two approaches resulted in almost the same excretion factors for layers, and the average nutrient excretion factors of layers (g/day/head) estimated were: N, 2.20; P, 0.55; K, 0.68; Mg, 0.23. The estimated excretion factors for N (only) are smaller than the reported factors.